Contracting for Control of Landscape- Level Resources - Schulz, Karen Bradshaw; Lueck, Dean (Iowa law review, 2015)
Environmental governance increasingly focuses on public-private partnerships. We focus on contracting as a subset of the role of private actors governing landscape-level resources-such as wildlife habitats, scenic vistas, and firescapes-that exceed individual parcel sizes and are thus difficult for individual landowners to control unilaterally. Numerous contractual arrangements have emerged to exert coordinated control over landscape-level resources. We hypothesize that variations in laws and transaction costs, which are controlled largely by the homogeneity of landowner preferences across fragmented parcels, drive private control of landscape-level resources. In the absence of effective private control, government agencies may assume control of the landscape-level resources. A series of case studies discusses how law shapes the conditions that favor private contracting regimes of landscape-level resources, which highlight broader themes of law as a catalyst for new governance.